History Wars The Peter Ryan - Manning Clark Controversy - Munro, Doug (ANU Press, 2021)
In 1993, Manning Clark came under severe (posthumous) attack in the pages of Quadrant by none other than Peter Ryan, who had published five of the six volumes of Clark's epic A History of Australia. In applying what he called "an overdue axe to a tall poppy", Ryan lambasted the History as "an imposition on Australian credulity" and declared its author a fraud, both as a historian and a person. This unprecedented public assault by a publisher on his best-selling author was a sensation at the time and remains lodged in the public memory. In History Wars, Doug Munro forensically examines the right and wrongs of Ryan's allegations, concluding that Clark was more sinned against than sinning and that Ryan repeatedly misrepresented the situation. More than just telling a story, Munro places the Ryan-Clark controversy within the context of Australia's History Wars. This book is an illuminating saga of that ongoing contest.' - James Curran, University of Sydney 'The Ryan-Clark controversy ... speaks to the place of Manning Clark in Australia's national imagination. Had Ryan taken his axe to another historian, it's unlikely that we would be still talking about it 30 years later. But Clark was the author and keeper of Australia's national story, however imperfect his scholarship and however blinkered that story. Few, if any, historians in the Anglo-American world have occupied the space that Clark occupied by dint of will, force of personality, and felicity of pen.' - Donald Wright, University of New Brunswick